Total dissolved solids modeling in the Shatt Al-Basrah canal, using Mike 11 - Lafta, A.A.; Al-Aeaswi , Q.M.F.; Al-Taei, S.A.R. (Mesopotamian Journal of Marine Sciences, 2022)
The application of one dimensional model is presented to simulate the distribution of total dissolved solids in the Shatt Al-Basrah canal using Mike11. The model was being run for 22 days with time step ∆t=60 sec and ∆x=200m. The hydrodynamic behavior and TDS distribution were studied for two time periods, the first period was represented the high flow period due to drying of the marshes and the second period was the period after opening the Nasiriyah drainage pump station in Dhi-Qar province. The model was calibrated in two site of the canal, the first locate before Al-Basrah high way bridge and the second locate near Al-Zubair bridge. The result of the model was in a good agreement with the field data of water level and TDS distribution.